2005
DOI: 10.1007/s11745-005-1452-7
|View full text |Cite
|
Sign up to set email alerts
|

Dietary sitostanol and campestanol: Accumulation in the blood of humans with sitosterolemia and xanthomatosis and in rat tissues

Abstract: Dietary sitostanol has a hypocholesterolemic effect because it decreases the absorption of cholesterol. However, its effects on the sitostanol concentrations in the blood and tissues are relatively unknown, especially in patients with sitosterolemia and xanthomatosis. These patients hyperabsorb all sterols and fail to excrete ingested sitosterol and other plant sterols as normal people do. The goal of the present study was to examine the absorbability of dietary sitostanol in humans and animals and its potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 28 publications
(23 reference statements)
2
10
1
2
Order By: Relevance
“…Both controls and heterozygotes seemed to have sufficient capacity to excrete stanols as suggested by the very low stanol serum levels, even after the subjects had consumed the diet enriched in stanols. This is in contrast to sitosterolemia patients, who show distinctly higher serum levels of sitostanol and campestanol on diets enriched in stanols (Connor et al, 2005).…”
Section: Discussioncontrasting
confidence: 66%
“…Both controls and heterozygotes seemed to have sufficient capacity to excrete stanols as suggested by the very low stanol serum levels, even after the subjects had consumed the diet enriched in stanols. This is in contrast to sitosterolemia patients, who show distinctly higher serum levels of sitostanol and campestanol on diets enriched in stanols (Connor et al, 2005).…”
Section: Discussioncontrasting
confidence: 66%
“…200 mg/day) diet. This result is also in part supported by the study of Connor et al [49] which showed that intake of 5 g/kg diet of phytostanols for 4 weeks had no effect on plasma cholesterol levels in Wistar rats compared to control diet. As mentioned earlier, Cyp27a1 is the rate-limiting enzyme for the conversion of cholesterol into bile acids [42] , and Abca1 is responsible for the reverse cholesterol transport of cholesterol from peripheral tissues to the liver for elimination in bile [25] .…”
Section: Discussionsupporting
confidence: 68%
“…Second, we also evaluated the effects of plant stanols, because sitosterolemic patients not only have increased serum plant sterol concentrations but also increased serum plant stanol concentrations. As recently indicated by Connor et al (21), plant stanols also are highly absorbed by sitosterolemic subjects and show a prolonged retention time. However, in epidemiological studies, serum plant stanol concentrations are frequently not reported, because sitostanol and campestanol concentrations are much lower and consequently difficult to measure.…”
Section: Discussionmentioning
confidence: 66%